Critical Neuroscience and Socially Extended Minds. (January 2015) - Slaby, Jan; Gallagher, Shaun
The concept of a socially extended mind suggests that our cognitive processes are extended not simply by the various tools and technologies we use, but by other minds in our intersubjective interactions and, more systematically, by institutions that, like tools and technologies, enable and sometimes constitute our cognitive processes. In this article we explore the potential of this concept to facilitate the development of a critical neuroscience. We explicate the concept of cognitive institution and suggest that science itself is a good example. Science, through various practices and rules, shapes our cognitive activity so as to constitute a certain type of knowledge, packaged with relevant skills and techniques. To develop this example, we focus on neuroscience, its cultural impact, and the various institutional entanglements that complicate its influence on reframing conceptions of self and subjectivity, and on defining what questions count as important and what kind of answers will be valued.